The Development of Parallel Declension Forms Inherited from Ancient Armenian in Modern Eastern Armenian - Dilbaryan, Narine (Bulletin of Yerevan University B: Philology, 2022)
Parallel declension forms are defined as a set of more than one posterior endings, morphemes used to express the same grammatical meaning. Accordingly, all indirect cases can have parallel forms: genitive, dative, ablative, instrumental, locative. Parallelisms in normative grammar can be equivalent and not equivalent. The reasons for the occurrence of case parallelisms are mainly intralinguistic: this is the simultaneous coexistence and competition of the grammatical systems of the previous literary languages, especially Old Armenian, dialects, as well as the Western Armenian language. It’s necessary for regulation parallelisms and maintaining the language norm, state or at least advisory institutions with clear functions and powers established by law.